Comparative characteristics of national and international legislation on mediation (Journal of actual problems of jurisprudence, 2018)
The aim of the study is to pose, study the development of the judicial mediation in Kazakhstan. In order to achieve the above objectives, we decided to define the role of the judicial mediation in the courts of general jurisdiction, to determine the content of a single information portal mediation. Explore the norms of Kazakhstani and foreign law, which govern relations mediation, law enforcement practices and scientific views in this sphere.Key words: mediation, mediation models.